Er rare-earth ion incorporation in sol-gel SnO2 - Morais,Evandro Augusto (2003)
Er-doped SnO2 thin films and xerogels are obtained by sol-gel technique. In order to understand the Er³+ rare-earth ion activity in SnO2 matrix, a characterization of Er incorporation is done through emission and excitation spectra of xerogels, besides thin film electrical characterization. Effects to grain dimensions are also analyzed based on X-ray diffraction data showing the particle growth with annealing temperature and inhibition of this growth by Er doping. Electrical characterization results suggest that Er³+ has an acceptor-like character in SnO2, and that codoping with Yb³+ allows an energy transfer process Yb³+ -> Er³+.